2017
DOI: 10.1177/0020852317692138
|View full text |Cite
|
Sign up to set email alerts
|

Public managers’ networking and innovative work behavior: the importance of career incentives

Abstract: From theories on middle managers’ entrepreneurship in private organizations, it is known that the structural network position of middle managers influences their innovative work behavior. Our study investigates if in a governmental setting, the intra-organizational networking behavior of public managers has a similar positive influence on innovative work behavior. As networking mechanisms may depend on the particular context and organizational norms, we also investigate the influence of networking motivations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…As career potential is a part of employability, a positive linkage assumption could be made regarding career management and innovative work behaviour. Furthermore, Zandberg and Morales [97] found that when aiming at increasing innovative behaviour, individual career motives seem to have stronger positive effects than collective motivations (such as teamwork-related motivations). In general, career supports employee wellbeing.…”
Section: Training and Development And Innovative Work Behaviourmentioning
confidence: 99%
“…As career potential is a part of employability, a positive linkage assumption could be made regarding career management and innovative work behaviour. Furthermore, Zandberg and Morales [97] found that when aiming at increasing innovative behaviour, individual career motives seem to have stronger positive effects than collective motivations (such as teamwork-related motivations). In general, career supports employee wellbeing.…”
Section: Training and Development And Innovative Work Behaviourmentioning
confidence: 99%
“…Management scholars have focused on employees’ psychological empowerment (Rehman et al , 2019), collective motive and career motive (Zandberg and Morales, 2019) as pivotal mechanisms behind employee innovative behavior. Scholars have underlined the magnitude of passion in the hospitality service sector (Ye et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given the cloud adoption offers significant benefits to healthcare, governments should provide incentives to healthcare organizations to actively adopt cloud. Many studies including both the government and private sector consistently demonstrate that providing incentives increase innovations in any government and private organizations [ 190 , 191 , 192 ]. However, policymakers should specifically focus on medium and small hospitals, including clinics, which experience the slowest pace of cloud adoption.…”
Section: Discussionmentioning
confidence: 99%